Erosion of orogenic wedges - a sandbox view - PERSSON, K. S.; SOKOUTIS, D. (Bulletin of the Geological Society of Greece, 2001)
Sandbox models give insights into the progressive development of two-sided orogenic wedges. Effective indenters, that develop in models without erosion for rigid indenter face-dips of 75 ° or 15 °, are strongly affected by erosion. No effective indenters develop in models with moderate and total erosion when the rigid indenter face-dip is 75°. In models with rigid indenter face-dips of 15° effective indenters develop but are smaller in size when erosion is applied. If the effective indenter is smaller, strain partitioning by compaction decreases in favor of strain partitioning by imbricate shear. Models with rigid indenter face-dips of 15° and 30° and without redeposition favor strain partitioning by development of new shears.